2018
DOI: 10.1176/appi.ps.201700407
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Treatment Reengagement for Veterans With Serious Mental Illness: Evaluating the Effectiveness of SMI Re-Engage

Abstract: SMI Re-Engage contact facilitated return to VHA care. SMI Re-Engage exemplifies how population health strategies can address health care discontinuities among people with serious mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The present results are not directly comparable to prior research findings because of the limited investigations regarding outreach efforts to patients with serious mental illness who are lost to care. However, the number of average contact attempts differentiating high ( M = 4.15) versus low ( M = 2.84) performing sites is consistent with other SMI Re-Engage program evaluation data which demonstrated that, among Veterans successfully contacted by clinicians, 89–92% were reached in five or fewer contact attempts whereas only 72%–75% were reached in three or fewer contact attempts (Abraham, 2019). Collectively, these data indicate that a best practice for contacting Veterans with serious mental illness who have been out of VHA care for at least 1 year is to make a minimum of four contact attempts using the methods described above.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present results are not directly comparable to prior research findings because of the limited investigations regarding outreach efforts to patients with serious mental illness who are lost to care. However, the number of average contact attempts differentiating high ( M = 4.15) versus low ( M = 2.84) performing sites is consistent with other SMI Re-Engage program evaluation data which demonstrated that, among Veterans successfully contacted by clinicians, 89–92% were reached in five or fewer contact attempts whereas only 72%–75% were reached in three or fewer contact attempts (Abraham, 2019). Collectively, these data indicate that a best practice for contacting Veterans with serious mental illness who have been out of VHA care for at least 1 year is to make a minimum of four contact attempts using the methods described above.…”
Section: Discussionsupporting
confidence: 86%
“…Smith et al acknowledged that a variety of factors likely influenced whether someone returned to care and that their analysis did not allow them to differentiate between client and clinician factors. An evaluation of the SMI Re-Engage program documented similar bivariate results—42% of Veterans who were contacted by LRCs had returned to care within 18 months as compared with 27% of Veterans whom LRCs attempted to reach but could not contact (Abraham et al, 2018). In the evaluation of SMI Re-Engage, the association between contact and return to care remained significant after statistical adjustments for the propensity to be contacted and patient-level factors, indicating the effectiveness of the outreach intervention (Abraham et al, 2018).…”
Section: Outreach Interventions For People With Serious Mental Illnessmentioning
confidence: 85%
See 1 more Smart Citation
“…Given the importance of ongoing care for individuals with SMI, in 2012 the VHA established the veterans with Serious Mental Illness Re-Engagement program (SMI Re-Engage) to facilitate treatment reengagement for veterans with SMI who once received VHA care and have not been seen in care for at least 12 months (Abraham, Bowersox, Visnic, & McCarthy, 2015; Department of Veterans Affairs, 2012; Kilbourne et al, 2014). This followed from a VHA Office of Medical Inspector (OMI) quality improvement project, conducted from 2007 to 2009, which sought to identify and contact veterans with SMI who had been lost to care for 1 year or more and invite them to return to VHA care.…”
mentioning
confidence: 99%
“…Thus, achieving contact with veterans is a core element of the program and may be a critical first step toward the goal of reengagement and ultimately improved health outcomes. An initial evaluation of the first 18 months of SMI Re-Engage program found that clinicians were able to contact 31% of veterans whom they attempted to reach (Abraham et al, 2015). To date, little is known regarding predictors of outreach contact.…”
mentioning
confidence: 99%